2019
DOI: 10.1089/biores.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Alliance in a Single Versus Group Rehabilitative Setting After Breast Cancer Surgery: Psychological Profile and Performance Rehabilitation

Abstract: The survival rate of women after breast cancer has improved significantly worldwide. More attention should be paid to the rehabilitation intervention after surgery. Cancer rehabilitation helps breast cancer survivors maintain the highest possible physical, social, psychological, and vocational function in the limits that are imposed by the cancer and its treatments. The aim of our research was to determine the rehabilitative setting that promotes greater efficacy of the rehabilitation. A double-blind, randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Several exercise programs have been proposed to reduce BCF (17,(32)(33)(34)(35)(36). However, the choice of the most appropriate intervention to offer remains troubled in real-life clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several exercise programs have been proposed to reduce BCF (17,(32)(33)(34)(35)(36). However, the choice of the most appropriate intervention to offer remains troubled in real-life clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer survivors are suffering many problems with the complications of surgery and radiation therapy such as Axillary web syndrome, pain, limited range of motion and dysfunction of the upper limbs, posture imbalance, lymphedema, or psychological symptoms associated with those conditions. The rehabilitation approach is effective for these sequelas [ 1 7 ]. The strong association between physical activity and all-cause mortality risk in breast cancer survivors [ 8 ] has led experts to recommend that breast cancer survivors engage in physical activity and exercise [ 9 ] and prompted researchers to investigate exercise interventions for this population.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a recent metanalysis investigating the pre and postdiagnosis physical activity on survival outcomes for different cancer types, showed that for breast cancer patients, there was a greater reduction in cancer-specific and all-cause mortality for postdiagnosis as compared to pre-diagnosis physical activity [ 4 ]. Of note, physical activity in the period following surgery, during and after adjuvant chemotherapy, if any, is associated with psychological benefits, especially when a therapeutic alliance is created between the patient and the technical operator who supervises this activity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%